Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Boycott Divestment Sunctions (BDS) pada Perusahaan Terdampak yang Go-Public di Bursa Efek Indonesia - Lilis Damayanti Sjam Radjak; Gaffar Gaffar; Ayu Rakhma Wuryandini (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the differences in financial performance before and after the Boycott Divestment Sanctions (BDS) movement in affected companies listed on the Indonesia Stock Exchange. Financial performance is measured using three main indicators: Market Value Added (MVA), Economic Value Added (EVA), and Earnings Per Share (EPS). This study used a quantitative method with a purposive sampling technique on 15 companies in the consumer cyclical and consumer non-cyclical sectors that met the criteria for being affected by BDS. Data, consisting of quarterly financial reports for the 2021–2024 period, were analyzed using the Wilcoxon Signed Rank Test to determine the differences before and after the BDS. The test results showed that MVA and EVA decreased significantly after the BDS, reflecting a decrease in the company's market value and economic value due to increased risk perception and a decrease in net operating profit after tax (NOPAT). Conversely, EPS showed no significant difference, indicating the company's ability to maintain stable earnings per share despite external pressures. This finding aligns with signaling theory, which states that external events can be negative signals for investors, but market reactions are heavily influenced by company fundamentals and management strategy.